Paleopole Reconstruction of Martian Magnetic Field Anomalies. Issue 5 (11th May 2018) - Thomas, Paul; Grott, Matthias; Morschhauser, Achim; Vervelidou, Foteini
Abstract: The crust of Mars shows strong remanent magnetization, which was likely acquired during the early phases of planetary evolution when a core dynamo still operated. The direction of the field responsible for magnetizing the crust holds clues to the working of the dynamo and the rotational dynamics of the planet. By analyzing individual crustal magnetic field anomalies and with the aid of additional assumptions, the field orientations can be reconstructed. We have implemented an Equivalent Source Dipole method to determine the main field orientation during magnetization, assuming that the considered anomalies are unidirectionally magnetized without making specific assumptions about the source geometry. The available data are fit in a least squares sense, and the method yields confidence intervals for the admissible paleopole locations. The method was applied to six crustal magnetic field anomalies, two of which require a south pole in the northern hemisphere, while three indicate a south pole in the southern hemisphere. This implies that polar reversals took place at least once in Martian history. Furthermore, one of the investigated anomalies requires a south pole at equatorial to midlatitudes, indicating that a significant amount of true polar wander must have occurred on Mars. Finally, tests with synthetic data indicate that admissible paleopole locations typically spread across at least 25% of the planet, which may partially explain the scatter found in previously published paleopole studies. Plain Language Summary: Today, the crust of Mars is strongly magnetized, and magnetization was likely acquired when a core dynamo still operated. In this study, the crustal magnetization is investigated and inferences about the former global magnetic field are made. To this end, we have implemented a method to synthesize the local sources of crustal magnetization and determined the former main field orientation. The method was applied to six crustal magnetic field anomalies, two of which require a former magnetic south pole in the northern hemisphere, while three indicate a former magnetic south pole in the southern hemisphere. This implies that at least once in the Martian history the magnetic north and south poles switched places. Furthermore, one of the investigated anomalies requires a former magnetic south pole at equatorial to midlatitudes, indicating that the rotational axis of Mars must have altered its alignment significantly. Key Points: We use an Equivalent Source Dipole method to investigate six Martian crustal magnetic field anomalies Results indicate that at least one polar reversal event must have occurred on Mars Mars must have furthermore experienced significant true polar wander